Penyelesaian Kredit dari Debitur Yang Meninggal Dunia Dengan Klaim Asuransi Jiwa - Evanti Andriani, Dwi; Iskandar, Hardian (UNES Law Review, 2023)
Collateral and insurance agreements are usually included with credit agreements. Banks can use this insurance agreement to transfer risk, especially life insurance if the debtor dies. If the debtor dies before paying off the remaining credit, the credit can also fall to his heirs. The purpose of this article is to study the legal consequences of a Bank Credit Agreement if the Debtor Dies and the Insurance Party's responsibilities regarding the Bank Credit Agreement if the Debtor Dies. This normative research uses a statutory and conceptual approach. The research results show that if the debtor dies, the credit agreement law cancels the credit because of the life insurance or life insurance clause. In other words, the insurance company must be responsible for paying off the remaining debt of the deceased debtor in accordance with the terms and conditions stated in the policy. In conclusion, the parties must understand the contents of the credit agreement well so that they know how to pay the debtor's remaining debt if this risk occurs.